PEMBUATAN RUANG INFORMASI BERBASIS GLAMPING (GLAMOROUS CAMPING) LITERASI SEBAGAI INFRASTRUKTUR EDU-GEOWISATA DI DESA OLUHUTA - Muhammad Ridho Kayambo; Intan Noviantari Manyoe; Reza Dwi Julianto Mohama; Nurul Istiqamah Kadekoh; Anisa Handani Uno; Nurvika Wahyuni S. Padodo; Febriyanto Padilaw Raza Kanna (Indonesian Collaboration Journal of Community Services, 2021)
Gorontalo province is one of the regions in Indonesia that is rich in geological, biological, and cultural diversity, especially Oluhuta Village, Kabila Bone Subdistrict, Bone Bolango Regency. Oluhuta village has 7 main potentials including Oluhuta Human Skeleton Site, Raised Ocean Site, Columnar joint, Petrosia lignosa (Salvador Dali),thousands of coral fish, various coral reefs, and turtles, making it suitable to be developed into a tourism area using the concept of edu-geotourism. The purpose of this article is to outline the stages in the creation of modern infrastructure, namely literacy glamping-based information space in Oluhuta Village as a hallmark of the concept of edu-geotourism developed to optimize tourism potential in  Oluhuta Village. The construction of this information space was carried out by the PHP2D SME Literacy team together with the Reformer Youth Movement or Oluhuta Village cadet reef. The result obtained is the creation of an information space that combines the concept of nature and the luxury of presenting information based on the principles of digital literacy and information known as glamping literacy, as a modern infrastructure edu-geotourism, so as to educate tourists and the public to always maintain and preserve the potentials in  Oluhuta Village